Perbedaan Penurunan Angka Kuman Dinding Setelah Didisinfeksi dengan Sinar Ultraviolet dan Pengkabutan Disinfektan "V" di Ruang Perawatan BP4 Kotagede Yogyakarta Tahun 2012 - Radityasari Nuraningtyas; Sri Muryani; Indah Werdiningsih (Sanitasi: Jurnal Kesehatan Lingkungan, 2012)
Patients, visitors, and workers at BP4 Kotagede are at risk of contracting respiratory and lung diseases. Based on the preliminary survey it was revealed that wall microbe number in nursingexceeded the maximum permitted by the regulation, and so that need to be controlled. Disinfection is one of the methods. The study was aimed to determine the difference in the reductionof microbe numbers between the use of UV sterilizer and disinfectant ‘V” by conducting an experiment which followed pre-test post-test only design. Samples were taken from each wall’s central point at one meter height of five nursing wards. Samples were taken in seven repetitions byusing wall swab method. The results showed that UV disinfection was able to decrease the wallmicrobe number in average of 47.185 % (p<0,,001). However, since the post-test measurementwere still 62,2 CFU/cm2, it was considered that this method had not fulfilled the requisite yet. Onthe other hand, disinfectant “V” was able reducing the microbe number in average of 93.74 %(p<0,001) and had met the requirement because the post treatment was below the thresholds,i.e.in average of 6.28 CFU/cm2.